2010
DOI: 10.1177/1461444809346720
|View full text |Cite
|
Sign up to set email alerts
|

The structure of international music flows using network analysis

Abstract: Using network analysis, this study examines the current structure of international music trade flow and its determinants. International music trade data from the United Nations Commodity Trade Statistics database are employed to describe the international music flow network and how it changed between 2002 and 2006. Network analysis reveals the imbalance of international music trade between the core and the periphery. Specifically, the USA and European countries including Germany, the UK and the Netherlands are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 42 publications
1
10
0
Order By: Relevance
“…Although our data cover only 47 countries and information on their telephone communication networks, this network depiction is consistent with prior maps of global communications (Barnett et al., 2001; Barnett and Sung, 2005a, 2005b). This pattern is also largely consistent with other patterns of exchanges such as news, films, student flows, patents, trademarks and software, migration, Intergovernmental Organizations (IGOs), trade, air passengers, mail and freight, international aid, arms, conflict, music, books, capital and scientific co-authorships (Barnett and Choi, 1995; Barnett et al., 2001; Chen and Barnett, 2000; Kim and Barnett, 1996, 2000, 2007; Lim et al., 2008; Moon et al., 2010; Nam and Barnett, 2011; Salisbury and Barnett, 1999).…”
Section: Data and Measuressupporting
confidence: 76%
“…Although our data cover only 47 countries and information on their telephone communication networks, this network depiction is consistent with prior maps of global communications (Barnett et al., 2001; Barnett and Sung, 2005a, 2005b). This pattern is also largely consistent with other patterns of exchanges such as news, films, student flows, patents, trademarks and software, migration, Intergovernmental Organizations (IGOs), trade, air passengers, mail and freight, international aid, arms, conflict, music, books, capital and scientific co-authorships (Barnett and Choi, 1995; Barnett et al., 2001; Chen and Barnett, 2000; Kim and Barnett, 1996, 2000, 2007; Lim et al., 2008; Moon et al., 2010; Nam and Barnett, 2011; Salisbury and Barnett, 1999).…”
Section: Data and Measuressupporting
confidence: 76%
“…Such cultural distance can negatively impact exchanges (Fu, 2013; Straubhaar, 2014). Indeed, studies of media flows have drawn on the national culture framework of Hofstede (2001), which highlights several spatially enduring and collectively shared systems of values in societies, to show how such values can translate into localized consumer preferences for foreign cultural products such as film and popular music (Fu, 2013; Fu & Sim, 2010; Moon et al, 2010). Based on these theoretical insights, we postulate the following hypotheses:…”
Section: Theory and Hypothesesmentioning
confidence: 99%
“…Over the past decades, we have witnessed a clear increase in the exchange of cultural products across the globe, as evident in media trade studies of film (e.g., Fu, 2006; Fu & Sim, 2010) and music (Moon Barnett, & Lim, 2010), cross-national comparisons of the newspaper coverage of culture (Janssen, Kuipers & Verboord, 2008), and comparative analyses of popularity rankings of media products (e.g., Achterberg, Heilbron, Houtman, & Aupers, 2011; Fu, 2013). Yet empirical investigations of these trends mostly focus on the macro level (by analyzing aggregated data), thereby underestimating the multilayered structure and complexity of cultural globalization (Appadurai, 1996; Straubhaar, 2014), and neglecting the role of individual agents.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, media products distributed worldwide did not have global or hybrid characteristics, but were localized to meet the taste of the local market in his analysis. Moon, Barnett, and Lim (2010) also found that a country's economic development has considerable influence on the flow of international music content and noted no noticeable changes in the structural inequality between the core and the periphery for the 2002 -2006 period. In contrast to the political economy tradition, cultural studies place greater emphasis on individuals' cultural autonomy. World-system theory, dependency theory, and cultural imperialism tend to view audiences as cultural dupes directly influenced by American cultural products, whereas cultural studies provide individuals with greater agency, viewing them as having their own creativity and freedom to decode media messages and sometimes to reproduce them in a hybridized form.…”
Section: Theories Of Globalizationmentioning
confidence: 99%